2022
DOI: 10.32598/ijn.35.137.3063
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Self-Differentiation in the Relationship Between Moral Distress, Compassions Fatigue and Work-family Conflict in Nurses

Abstract: Background & Aims: Many nurses are involved in work-family conflicts due to the nature of the nursing profession and high workload. Identification of the factors related to work-family conflict can help reduce or control this conflict. Compassion fatigue and moral distress are some of the factors that may affect the work-family conflict of nurses. This study aims to determine the mediating role of self-differentiation in the relationship between compassion fatigue, moral distress and work-family conflict a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…One's perception of leaving the profession despite being in a job position is called "turnover intention" (9). Work issues, such as burnout, job dissatisfaction, job stress, and high work pressure, are factors affecting the desire to leave the nursing profession (3,10). In a study conducted in 82 ICUs in Europe, Piers et al (2011) reported a high level of futile care perception and introduced the increased turnover intention as one of the consequences of futile care (11).…”
Section: Introductionmentioning
confidence: 99%
“…One's perception of leaving the profession despite being in a job position is called "turnover intention" (9). Work issues, such as burnout, job dissatisfaction, job stress, and high work pressure, are factors affecting the desire to leave the nursing profession (3,10). In a study conducted in 82 ICUs in Europe, Piers et al (2011) reported a high level of futile care perception and introduced the increased turnover intention as one of the consequences of futile care (11).…”
Section: Introductionmentioning
confidence: 99%